GIT2 deficiency attenuates inflammation-induced expression of pro-labor mediators in human amnion and myometrial cells†. Issue 6 (27th March 2019) - Lim, Ratana; Lappas, Martha
Abstract: Untimely activation of the inflammatory response by sterile or infective insults in uterine tissues can result in preterm birth. Pro-inflammatory cytokines and pathogenic activation of toll-like receptors (TLRs) initiate a biochemical cascade of events leading to myometrial activation and contractility, cervical dilatation, and rupture of the chorioamniotic membranes. GIT2 is a signaling protein known to play a role in innate and adaptive immunity; however, its role in the inflammatory pathways of human labor is not known. In this article, we report that GIT2 expression is lower in human myometrium and fetal membranes with term labor, and in preterm amnion with histological chorioamnionitis. GIT2 knockdown by siRNA in primary myometrial and amnion cells exhibited reduced expression of pro-inflammatory cytokines and chemokines in response to inflammatory challenge by cytokines or TLR ligands. In addition, the pro-inflammatory cytokines IL1B and TNF could not induce the expression of extracellular matrix degrading enzymes in GIT2-deficient amnion cells. Myometrial activation in response to pro-inflammatory cytokines was also significantly suppressed in GIT2-deficient cells as evidenced by decreased prostaglandin release and expression of contraction-associated proteins. Further to this, collagen gel assays demonstrated that TNF had a reduced ability to induce myometrial contractility in situ in GIT2-deficient myometrial cells compared to control-transfected cells. In summary, the loss of GIT2 diminishes the effects inflammatory mediators have in promoting myometrial contraction and fetal membrane rupture in vitro, suggesting that GIT2 could be a possible target for preterm birth therapies. Abstract : The G protein-coupled receptor signaling protein GIT2 is involved in the genesis of inflammation-induced pro-labor mediators in myometrium and fetal membranes.